Role of Computed Tomography and Magnetic Resonance Imaging in the Diagnosis of Coronary Artery Disease: Indications and Applications - Bhatia, Mona; Kumar, Parveen (Indographics, 2022)
Coronary artery disease (CAD) is the leading cause of death worldwide. The diagnosis of CAD relies on the clinical history, electrocardiographic changes, and imaging findings. The available imaging methods include transthoracic echocardiography, computed tomography (CT), cardiac magnetic resonance (CMR) imaging, and invasive angiography. Over the last two decades, cardiac CT and CMR have emerged as promising noninvasive modalities in the assessment of patients with suspected and established CAD. Both the modalities have their own advantages and disadvantages which complement each other in comprehensive evaluation of CAD aiding in the diagnosis, guiding clinical decision-making, and improving risk stratification. In this article, we provide an overview of the techniques and clinical applications of cardiac CT and CMR imaging in the assessment of patients with CAD.
Keywords: coronary artery disease; computed tomography; magnetic resonance imaging